2021
DOI: 10.1002/adfm.202008306
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure and Electron Magnetic Circular Dichroism of Individual Rock Salt Structure Antiphase Boundaries in Spinel Ferrites

Abstract: Spinel ferrites are an important class of materials, whose magnetic properties are of interest for industrial applications. The antiphase boundaries (APBs) that are commonly observed in spinel ferrite films can hinder their applications in spintronic devices and sensors, as a result of their influence on magnetic degradation and magnetoresistance of the materials. However, it is challenging to correlate magnetic properties with atomic structure in individual APBs due to the limited spatial resolution of most m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…experimentally on various compounds [74]. Our results for NFO are in agreement with former DFT studies [30,32,75], which however only compared a very small number of wellordered inverse spinel structures. The predicted lowest energy space group of NFO also corresponds to that measured at 300 K on single crystals with Raman spectroscopy [70] or with synchrotron diffraction [71].…”
Section: Influence Of the Cation Distribution In The Occupied Oh Site...supporting
confidence: 91%
“…experimentally on various compounds [74]. Our results for NFO are in agreement with former DFT studies [30,32,75], which however only compared a very small number of wellordered inverse spinel structures. The predicted lowest energy space group of NFO also corresponds to that measured at 300 K on single crystals with Raman spectroscopy [70] or with synchrotron diffraction [71].…”
Section: Influence Of the Cation Distribution In The Occupied Oh Site...supporting
confidence: 91%
“…[ 32,33 ] Recently, Li et al. [ 51 ] also confirmed that the antiferromagnetic coupling interaction in the APB defects weakens the magnetism based on electron magnetic circular dichroism measurements and first‐principles density functional theory calculations. To confirm the existence of the antiferromagnetic phase in HEO thin film, the M – H loops of IP at 10 K for the 60 nm thick film were collected under an applied magnetic field cool by 1000 Oe (Figure 4h).…”
Section: Resultsmentioning
confidence: 98%
“…The interactions between the stimulus and chiral components change the chirality, manifesting as the change of g-factor and g lum values. 78,79 Typically, CD and CPL spectra enable quantifying the degree of the stimulus. As presented in Fig.…”
Section: Sensingmentioning
confidence: 99%